Creative Strategies for Digital Learning Media in Indonesian Language Learning - Wardhana, Eka; Rahayu, Ni Komang Suri; Santika, Ni Luh Putu; Octavyanti, Ni Putu Liana; Oktawiryati, Ni Putu; Sanjaya, Ida Bagus; Sudiana, I Nyoman (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The use of digital learning media in the context of Indonesian language learning is increasingly becoming the focus in efforts to improve the quality of education. This research investigates creative strategies in using digital media to enrich students' learning experiences. The research method used is descriptive analysis with a qualitative approach, using observation, interviews and documentation as data collection techniques. The research results show that digital learning media not only clarifies teaching material, but also succeeds in stimulating students' interest in learning, as well as improving learning outcomes in various aspects such as cognitive, affective and psychomotor. Teachers play an important role in selecting and implementing this media creatively to suit students' needs and characteristics. Thus, this research provides insight into the importance of technology integration in Indonesian language education and offers concrete examples of creative strategies that can be implemented to increase the effectiveness of learning in the digital era.Penggunaan media pembelajaran digital dalam konteks pembelajaran Bahasa Indonesia semakin menjadi fokus utama dalam upaya meningkatkan kualitas pendidikan. Penelitian ini menginvestigasi strategi kreatif dalam pemanfaatan media digital untuk memperkaya pengalaman belajar siswa. Metode penelitian yang digunakan adalah deskriptif analisis dengan pendekatan kualitatif, menggunakan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa media pembelajaran digital tidak hanya memperjelas materi ajar, tetapi juga berhasil merangsang minat belajar siswa, serta memperbaiki hasil belajar dalam berbagai aspek seperti kognitif, afektif, dan psikomotorik. Guru berperan penting dalam memilih dan mengimplementasikan media ini dengan kreatif agar sesuai dengan kebutuhan dan karakteristik siswa. Dengan demikian, penelitian ini memberikan wawasan tentang pentingnya integrasi teknologi dalam pendidikan Bahasa Indonesia serta menawarkan contoh konkret strategi kreatif yang dapat diterapkan untuk meningkatkan efektivitas pembelajaran di era digital.